The Key Macroeconomic Task and the Art of Economic Regulation - Tavadyan, A. A. (ՀՀ ԳԱԱ հրատ.)
Key indicators constitute nodes that link economic processes into one system. To obtain acceptable results in the study of economic interrelations, it is necessary to identify the uncertainty intervals of key indicators and their precise coupling. Առանցքային ցուցանիշները տնտեսության գործընթացները կապող հանգույցներն են: Տնտեսական փոխկապվածության հետազոտության ժամանակ անհրաժեշտ են առանցքային ցուցանիշների անորոշության միջակայքերի բացահայտումը և նրանց հստակ համակցումը:Ключевые индикаторы представляют собой узлы, связывающие экономические процессы в единую систему. Для получения приемлемых результатов при исследовании экономических взаимосвязей необходимо выявление интервалов неопределенности ключевых индикаторов и их четкая стыковка.
Keywords: Economics